2014
DOI: 10.1097/qad.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Do the epidemiology, physiological mechanisms and characteristics of hepatocellular carcinoma in HIV-infected patients justify specific screening policies?

Abstract: Reducing the incidence of hepatocellular carcinoma (HCC) in HIV-infected patients has become a serious problem when managing these patients. There are many explanations for this disease evolution, which notably include their longer survival under effective antiviral therapy and also the more rapid evolution of chronic liver disease. Despite recent advances in the management of hepatitis B (HBV) and hepatitis C (HCV) viral diseases, which will probably increase the number of patients achieving a virological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 105 publications
2
21
1
Order By: Relevance
“…As well as radiological prognostic factors, immunosuppression, well known to accelerate tumour progression, has been confirmed as constituting a higher risk of HCC, which was not supported by our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…As well as radiological prognostic factors, immunosuppression, well known to accelerate tumour progression, has been confirmed as constituting a higher risk of HCC, which was not supported by our study.…”
Section: Discussioncontrasting
confidence: 86%
“…We recently demonstrated that HCC present with more severe radiological features at diagnosis in HIV+/HCV+ than HIV−/HCV+ cirrhotic patients because of the frequent infiltrative types HCC with portal vein tumour thrombosis . The overall survival of patients who develop HCC is also significantly worsened in HIV+/HCV+ than HIV−/HCV+ patients . However, the therapeutic management and the analysis of prognostic factors for survival in prospective studies have not been taken into account to date.…”
Section: Introductionmentioning
confidence: 99%
“…Our case series shares common clinicopathological factors described in previously reported patient cohorts of HIV-associated HCC [26] . Equally, our results rely on the prospective collection of consecutive, unselected referrals to tertiary referral centres, where patients received state-of-the-art oncology and HIV care following multidisciplinary discussion.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, HIV proteins (tat, gp120) may act on hepatic stellate cells (HSC) to induce inflammation and contribute to fibrosis 93 . Genomic integration of HBV is present in the majority of cases in which HBV-infection leads to HCC 94 , and appears to be facilitated by DNA damage in the setting of chronic inflammation and oxidative stress.…”
Section: Etiologic Agents and Pathogenesismentioning
confidence: 99%